Dietary methionine restriction improves colon tight junction barrier function and alters claudin expression pattern - Ramalingam, Arivudainambi (Am J Physiol Cell Physiol, 2010)
The beneficial effects of caloric restriction in increasing longevity and forestalling age-related diseases are well known. Dietary restriction of methionine also renders similar benefits. We recently showed in a renal epithelial cell culture system that reduction of culture medium methionine by 80% resulted in altered tight junctional (TJ) claudin composition and also improved epithelial barrier function (51). In the current study, we examined the effect of dietary restriction of methionine on TJ barrier function in rat gastrointestinal tissue to see whether this phenomenon also holds true in a tissue model and for a different epithelial cell type. After 28 days on methionine-restricted (MR) diet, rats showed small but significant reductions in the plasma and (intracellular) colonocyte levels of methionine. Colon mucosal sheets from rats on the MR diet showed increased transepithelial electrical resistance with concomitant decrease in paracellular diffusion of (14)C-d-mannitol, suggesting improved barrier function relative to rats on control diet. This improved barrier function could not be explained by changes in colon crypt length or frequency. Neither was the colonocyte mitotic index nor the apoptotic frequency altered significantly. However, TJ composition/structure was being altered by the MR diet. RT-PCR and Western blot analysis showed an increase in the abundance of claudin-3 and an apparent change in the posttranslational modification of occludin, data reinforcing a paracellular barrier alteration. Overall, our data suggest that reduction in dietary intake of methionine results in improved epithelial barrier function by inducing altered TJ protein composition.